Insights into the magnetic origin of CunCr (n= 9÷11) clusters: A superposition of magnetic and electronic shells - Mai, Nguyen Thi; Lan, Ngo Thi; Tung, Nguyen Thanh (Vietnam Journal of Science and Technology, 2020)
Interests in Cu-Cr sub-nanometer systems have been increasing due to the recently-found icosahedral Cu12Cr cluster as a superatomic molecule, where the 3d-Cr and 4s-Cu electrons can phenomenologically form the 18-e molecular shell (1S21P61D10) of Cu12Cr. In this report, we set out to investigate the energetically-preferred geometries and stabilities of CunCr (n = 9÷11) clusters using the density-functional-theory calculations. It is found that not all of 3d-Cr electrons involve in the formation of the cluster shell and the remaining localized ones cause the magnetic moment of the clusters, which is different from what was believed.